Biological evaluation and finite-element modeling of porous poly(para-phenylene) for orthopaedic implants. (May 2018) - Ahn, Hyunhee; Patel, Ravi R.; Hoyt, Anthony J.; Lin, Angela S.P.; Torstrick, F. Brennan; Guldberg, Robert E.; Frick, Carl P.; Carpenter, R. Dana; Yakacki, Christopher M.; Willett, Nick J.
Graphical abstract: Abstract: Poly( para -phenylene) (PPP) is a novel aromatic polymer with higher strength and stiffness than polyetheretherketone (PEEK), the gold standard material for polymeric load-bearing orthopaedic implants. The amorphous structure of PPP makes it relatively straightforward to manufacture different architectures, while maintaining mechanical properties. PPP is promising as a potential orthopaedic material; however, the biocompatibility and osseointegration have not been well investigated. The objective of this study was to evaluate biological and mechanical behavior of PPP, with or without porosity, in comparison to PEEK. We examined four specific constructs: 1) solid PPP, 2) solid PEEK, 3) porous PPP and 4) porous PEEK. Pre-osteoblasts (MC3T3) exhibited similar cell proliferation among the materials. Osteogenic potential was significantly increased in the porous PPP scaffold as assessed by ALP activity and calcium mineralization. In vivo osseointegration was assessed by implanting the cylindrical materials into a defect in the metaphysis region of rat tibiae. Significantly more mineral ingrowth was observed in both porous scaffolds compared to the solid scaffolds, and porous PPP had a further increase compared to porous PEEK. Additionally, porous PPP implants showed bone formation throughout the porous structure when observed via histology. A computational simulation of mechanical push-out strength showed approximately 50% higher interfacial strength in the porous PPP implants compared to the porous PEEK implants and similar stress dissipation. These data demonstrate the potential utility of PPP for orthopaedic applications and show improved osseointegration when compared to the currently available polymeric material. Statement of significance: PEEK has been widely used in orthopaedic surgery; however, the ability to utilize PEEK for advanced fabrication methods, such as 3D printing and tailored porosity, remain challenging. We present a promising new orthopaedic biomaterial, Poly( para -phenylene) (PPP), which is a novel class of aromatic polymers with higher strength and stiffness than polyetheretherketone (PEEK). PPP has exceptional mechanical strength and stiffness due to its repeating aromatic rings that provide strong anti-rotational biaryl bonds. Furthermore, PPP has an amorphous structure making it relatively easier to manufacture (via molding or solvent-casting techniques) into different geometries with and without porosity. This ability to manufacture different architectures and use different processes while maintaining mechanical properties makes PPP a very promising potential orthopaedic biomaterial which may allow for closer matching of mechanical properties between the host bone tissue while also allowing for enhanced osseointegration. In this manuscript, we look at the potential of porous and solid PPP in comparison to PEEK. We measured the mechanical properties of PPP and PEEK scaffolds, tested these scaffolds in vitro for osteocompatibility with MC3T3 cells, and then tested the osseointegration and subsequent functional integration in vivo in a metaphyseal drill hole model in rat tibia. We found that PPP permits cell adhesion, growth, and mineralization in vitro. In vivo it was found that porous PPP significantly enhanced mineralization into the construct and increased the mechanical strength required to push out the scaffold in comparison to PEEK. This is the first study to investigate the performance of PPP as an orthopaedic biomaterial in vivo . PPP is an attractive material for orthopaedic implants due to the ease of manufacturing and superior mechanical strength.